Perceived causes and contributory conditions for perinatal death: perspectives of midwives, parents, and communities in Northwest Ethiopia—a qualitative study - Arega, Dawit Tiruneh; Gobena, Tesfaye; Assefa, Nega; Tura, Abera Kenay (Frontiers in Medicine, 2025)
BackgroundDespite many efforts to reduce perinatal death, it is common in low- and middle-income countries, including Ethiopia countries. Perinatal death has huge repercussions for parents and families, altering their self-esteem and ambitions related to parenting. Therefore, it is crucial to develop targeted and cost-effective interventions to reduce the burden of perinatal death.ObjectiveThis study aimed to investigate how midwives, parents, and communities perceive the causes and factors contributing to perinatal death in the Lay Gayint District of Northwest Ethiopia.MethodsA phenomenological study was conducted with 14 participants (midwives, parents, and community members). Study participants were recruited through purposive sampling guided by emerging themes. A probe guide was prepared to conduct the interviews and was piloted. Two trained data collectors gathered data using in-depth, face-to-face interviews from 1 November 2022 to 30 May 2023. Participants listened to the audio records, reviewed the transcripts, and provided feedback for accuracy. Each interview was recorded and lasted between 15 and 65 min. The data were analyzed using grounded theory and an inductive theme-building approach using NVivo-14 software.ResultsThree major themes emerged for the perceived causes of perinatal death: spiritual shadows, harmful traditional customs, and obstetric causes. Five major themes emerged as contributory factors: barriers to women’s empowerment, geographic and economic challenges, healthcare quality challenges, emotional turbulence, culture, and midwives as cultural mediators. This study proposed a new theory entitled “The dynamism of the culture, healthcare system, and midwifery practices in perinatal death.”ConclusionThis study emphasizes how healthcare, economic, and cultural factors interact to contribute to perinatal death, highlighting the crucial role of midwives as cultural mediators. This new theory proposes that culture, healthcare systems, and midwifery practices play a crucial role in perinatal death reduction. This study reflects the need for a multidisciplinary approach, culturally relevant interventions, and collaboration between stakeholders and cultural experts. This study provides policymakers with an understanding of how to build successful and targeted programs that consider cultural and economic costs and women’s empowerment, particularly for parents dealing with perinatal deaths.